Islamic Thought, Arabic Literature, and Civic Imagination in Nigeria: A Rhetorical and Pedagogical Analysis - Kankawi, Uthman Idrees; Fahm, AbdulGafar Olawale; Abdussalam, Uthman; Zubair, Abdulhakeem (Millah: Journal of Religious Studies, 2026)
This study examines the intricate intersection of Islamic thought and Arabic literature within the Nigerian context, highlighting their profound influence on cultural, religious, and intellectual paradigms. By tracing their historical evolution, the research reveals how these narratives have shaped identity formation, social cohesion, and education while remaining dynamic in the face of modern challenges. The analysis draws on historical texts, oral traditions, and contemporary works to illustrate the enduring adaptability of these traditions. Through a multidisciplinary approach, the study emphasises Nigerian Arabic literature's thematic richness and stylistic diversity, demonstrating its capacity to address contemporary issues such as corruption, gender equity, and social justice. The findings show the transformative potential of this interplay, with implications for education reform, cultural policy, and interfaith dialogue. Ultimately, this research contributes to a deeper understanding of Nigeria's intellectual heritage and offers pathways for leveraging this intersection to foster inclusivity and social harmony.